Comparison of delivery characteristics and obstetric outcomes of Syrian refugee pregnancies after a decade (Annals of Medical Research, 2023)
Aim: This research aims to compare and analyze the demographic, obstetric, and neonatal outcomes of Syrian refugees (SYR) and Turkish pregnant women.Materials and Methods: This retrospective cross-sectional study included 1,823 pregnant Turkish and Syrian women aged 13 to 47 who gave birth at a tertiary care facility in the Mediterranean region of Turkey. Between September 2020 and August 2021, 940 Turkish and 883 SYR pregnant women participated in the study. The groups were compared for demographic data, obstetric outcomes, and neonatal features.Results: The maternal age distribution for SYR includes younger ages (p